Mobile data gathering algorithms for wireless sensor networks - Ghaleb, Mukhtar Mahmoud Yahya (2014)
Data gathering is among the issues constantly acquiring attention in the area of Wireless Sensor Networks (WSNs) due to its impact and ability to transform many areas associated with the human life. There is a consistent increase in the research directed on the gains of applying mobile elements to collect data from sensors, especially those oriented to power issues as compared to multi-hop technique. There are two prevailing strategies used to collect data in sensor networks. The first approach requires data packets to be serviced via multi-hop relay to reach the respective Base Station (BS). The second strategy encompasses a mobile element which serves as the core element for the searching of data. These mobile elements will go to each transmission range of each respective sensor to upload its data. In this research, a Mobile Data Gathering based Network Layout (MDG-NL) algorithm is proposed. This algorithm enables shortened tour length for the respective mobile element. In addition, a certain number of nodes work as a temporary BS by aggregating the data packets from affiliated sensors via multi-hop. Furthermore, strategically divisioning the area of data collection, the optimization of the mobile element can be elevated. These derived areas are centric on determining the common configuration ranges strategically placing the collection point. Thus, within each of these areas, the multi-hop collection is deployed. This research presents a Zonal Data Gathering based Multi-hop and Mobile Element (ZDG-MME) algorithm to enhance the network lifetime. ZDG-MME algorithm is able to segment the deployment field into two divisions and forward the tailored data to the BS. First, the inner division which is the closest to the BS reports the sensed data directly through multi-hop. Second, the outer division reports the data to certain nodes selected as polling nodes. ZDG-MME algorithm is designed to ensure minimizing both the energy consumption and the data gathering latency whilst avoiding the hotspot area. The third proposed algorithm achieves an adaptive data gathering strategy. In this algorithm, the user has to tune an appropriate variable which directly affects the power consumption and the data gathering latency. This variable is a trade-off parameter that balances between the energy consumption and data gathering latency. The selection of this parameter is based on the application requirements. Minimal Constrained Rendezvous Node (MCRN) algorithm is designed to ensure that the number of pause locations for the mobile element is minimized. In MCRN, the selecting of rendezvous nodes is based on three factors: 1) bounded relay hop 2) number of affiliation nodes 3) distance of the respective rendezvous node to the BS. The algorithm is proven to minimize the number of rendezvous nodes which ensure that the tour length and the data gathering latency are both minimized. The performance evaluation of the proposed data gathering algorithms has been done through a detailed and extensive discrete-event-simulation analysis. The acquired results show that the MDG-NL scheme significantly improves the performance over SPT-DGA up to 12.5%. The results obtained by the ZDG-MME shows an enhancement on the performance up to 15.21%. The results have proven the enhancements achieved by the proposed algorithms through the performance metrics of tour length, data gathering latency and total energy consumed.